2015
DOI: 10.1093/ofid/ofv111
|View full text |Cite|
|
Sign up to set email alerts
|

Inhaled Nitric Oxide as an Adjunctive Treatment for Cerebral Malaria in Children: A Phase II Randomized Open-Label Clinical Trial

Abstract: Treatment with inhaled nitric oxide as an adjuvant therapy for pediatric patients with cerebral malaria for 48 hours did not result in a significant difference in plasma Angiopoietin-1 levels when compared with placebo in a phase II open-label clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Various attempts to improve NO bioavailability have included the use of L-arginine, a precursor for NO synthesis (16), and inhaled NO (23,24). However, despite initial enthusiasm (24), inhaled NO failed to reduce markers of endothelial activation in either a randomized placebocontrolled trial (25) or an open-label trial (26), presumably reflecting the inability of this modality to deliver NO bioactivity to relevant microvascular beds and immune targets.…”
mentioning
confidence: 99%
“…Various attempts to improve NO bioavailability have included the use of L-arginine, a precursor for NO synthesis (16), and inhaled NO (23,24). However, despite initial enthusiasm (24), inhaled NO failed to reduce markers of endothelial activation in either a randomized placebocontrolled trial (25) or an open-label trial (26), presumably reflecting the inability of this modality to deliver NO bioactivity to relevant microvascular beds and immune targets.…”
mentioning
confidence: 99%
“…The second study compared 46 children receiving iNO at 80 ppm with 46 children in the placebo group, with similar results. Plasma levels of Ang-2 and inflammatory cytokines remained similar between groups, and there was no difference in mortality (19). Treatment with iNO resulted in increased levels of plasma nitrate, and methemoglobinemia developed, but without sequelae.…”
Section: Nitric Oxidementioning
confidence: 80%
“…Given that iNO is used in the treatment of other diseases, with a well-established safety profile and low cost, along with positive results in animal models, it is an attractive option for clinical tests in malaria patients. Based on these advantages, two randomized phase II clinical trials in patients with severe malaria have been recently reported in Uganda (18,19,75). The first study compared 88 children who received iNO at 80 ppm with 92 children who received placebo (all subjects received artesunate i.v.)…”
Section: Nitric Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…1 They are also made with universities in countries where we implement research activities, such as Mbarara University of Science and Technology (MUST), and with international universities, including Harvard University, with whom Epicentre ran a clinical trial to improve the management of the treatment of children with severe malaria in Uganda (Mwanga-Amumpaire et al 2015). In some cases partnerships with private and/or nongovernmental organisations are formed.…”
Section: Introductionmentioning
confidence: 99%